Anthocyanin Extraction and Purification from Red Onion Peels (Allium cepa) and Its Applications Against the CAL-51 Cell Line - Latteef, Noor S.; Ghassan M. Ahmed; Essam F. Aljumili (International Journal of Medical Toxicology and Forensic Medicine, 2026)
Background: Red onion (Allium cepa L.) peels represent an abundant agricultural byproduct rich in bioactive flavonoids, yet their therapeutic potential against aggressive breast cancer models remains poorly characterized. This study aimed to extract and purify anthocyanins from red onion peels, characterize their active constituents, and evaluate their selective in vitro cytotoxicity against the triple-negative breast cancer (TNBC) cell line CAL-51 relative to non-tumorigenic Normal Human Fibroblast (NHF) cells. Methods: Anthocyanins were extracted with acidified aqueous ethanol, purified using silica gel G60 column chromatography and characterized by reversed-phase high-performance liquid chromatography (RP-HPLC). Cytotoxicity was evaluated through 72-hour MTT assays on CAL-51 and NHF cells, confirmed by phase-contrast morphological analysis and analyzed using one-way ANOVA. Results: Through RP-HPLC, malvidin and peonidin were characterized as the major monomeric anthocyanidins. According to the results, the purified extract demonstrated a potent and cell line-dependent dose effect for the cytotoxicity of CAL-51 cells with IC50 = 247.5 μg/mL (maximum inhibition: 63.73% at 1000 µg/mL), accompanied by morphological hallmarks of apoptosis. In contrast, the extract exhibited much lower toxicity against NHF cells (IC50=1767 µg/mL; maximum inhibition: 17.39% at 10,000 µg/mL), resulting in a good selectivity index of 7.1. Conclusion: Purified red onion peel anthocyanins were powerful, selective anti-proliferative and pro-apoptotic agents against TNBC in vitro without harming normal cells. This sets a path to exploiting agricultural waste as a source of potential natural therapeutic agents for the individualised treatment of breast cancer in an economically viable manner.